Effect of crop residue returns on N2O emissions from red soil in China. (18th October 2015) - Wu, Y.; Lin, S.; Liu, T.; Wan, T.; Hu, R.
Abstract: For a long time, farmers in the red soil region of southern China have returned crop residues to the soil, but how various crop residues influence nitrous oxide (N2 O) emissions is not well understood. We compared the influence of returning different crop residues [rapeseed cake (RC), maize straw, rice straw and wheat straw (WS)] in combination with different levels of nitrogen (N) fertilizer (nil, low and high) on red soil N2 O emissions. Results confirmed the inverse relationship between cumulative N2 O emissions and residue C:N ratio in red soil under different levels of N fertilizer. However, N‐fertilizer application did not significantly influence N2 O emissions in the WS (which had the highest C:N ratio) and corresponding control treatments, while it enhanced N2 O emissions in the RC (which had the lowest C:N ratio) treatment and displayed significantly higher cumulative N2 O emissions with low N fertilizer application. This phenomenon may be attributed to the poor nutrient content in red soil, which leads to 'Liebig's Law of the Minimum' on available C. N fertilizer application provided sufficient available N, while the readily available C, which was mainly dependent on the degradability of the residue, became the crucial factor influencing N2 O emissions. Additional experiments, which showed that the addition of glucose and sucrose could increase N2 O emissions when N ( NH 4 + − N ) was sufficient, confirmed this hypothesis. Thus, to reduce N2 O emissions when returning residues to red soil, we suggest that both the residue C:N ratio and the quality should be considered when deciding whether to apply N fertilizer.